Meta-analysis of GWAS of over 16,000 individuals with autism spectrum disorder highlights a novel locus at 10q24.32 and a significant overlap with schizophrenia - Autism Spectrum Disorders Working Group of The Psychiatric Genomics Consortium (2017)
Autism Spectrum Disorders Working Group of The Psychiatric Genomics Consortium - Collaborators (162): Anney RJL, Ripke S, Anttila V, Grove J, Holmans P, Huang H, Klei L, Lee PH, Medland SE, Neale B, Robinson E, Weiss LA, Zwaigenbaum L, Yu TW, Wittemeyer K, Willsey AJ, Wijsman EM, Werge T, Wassink TH, Waltes R, Walsh CA, Wallace S, Vorstman JAS, Vieland VJ, Vicente AM, vanEngeland H, Tsang K, Thompson AP, Szatmari P, Svantesson O, Steinberg S, Stefansson K, Stefansson H, State MW, Soorya L, Silagadze T, Scherer SW, Schellenberg GD, Sandin S, Sanders SJ, Saemundsen E, Rouleau GA, Rogé B, Roeder K, Roberts W, Reichert J, Reichenberg A, Rehnström K, Regan R, Poustka F, Poultney CS, Piven J, Pinto D, Pericak-Vance MA, Pejovic-Milovancevic M, Pedersen MG, Pedersen CB, Paterson AD, Parr JR, Pagnamenta AT, Oliveira G, Nurnberger JI, Nordentoft M, Murtha MT, Mouga S, Mortensen PB, Mors O, Morrow EM, Moreno-De-Luca D, Monaco AP, Minshew N, Merikangas A, McMahon WM, McGrew SG, Mattheisen M, Martsenkovsky I, Martin DM, Mane SM, Magnusson P, Magalhaes T, Maestrini E, Lowe JK, Lord C, Levitt P, Martin CL, Ledbetter DH, Leboyer M, LeCouteur AS, Ladd-Acosta C, Kolevzon A, Klauck SM, Jacob S, Iliadou B, Hultman CM, Hougaard DM, Hertz-Picciotto I, Hendren R, Hansen CS, Haines JL, Guter SJ, Grice DE, Green JM, Green A, Goldberg AP, Gillberg C, Gilbert J, Gallagher L, Freitag CM, Fombonne E, Folstein SE, Fernandez B, Fallin MD, Ercan-Sencicek AG, Ennis S, Duque F, Duketis E, Delorme R, DeRubeis S, DeJonge MV, Dawson G, Cuccaro ML, Correia CT, Conroy J, Conceição IC, Chiocchetti AG, Celestino-Soper PBS, Casey J, Cantor RM, Café C, Bybjerg-Grauholm J, Brennan S, Bourgeron T, Bolton PF, Bölte S, Bolshakova N, Betancur C, Bernier R, Beaudet AL, Battaglia A, Bal VH, Baird G, Bailey AJ, Bækvad-Hansen M, Bader JS, Bacchelli E, Anagnostou E, Amaral D, Almeida J, Børglum AD, Buxbaum JD, Chakravarti A, Cook EH, Coon H, Geschwind DH, Gill M, Hallmayer J, Palotie A, Santangelo S, Sutcliffe JS, Arking DE, Devlin B, Daly MJ.